2023
DOI: 10.1021/acsami.3c07770
|View full text |Cite
|
Sign up to set email alerts
|

Sub-Micrometer Phonon Mean Free Paths in Metal–Organic Frameworks Revealed by Machine Learning Molecular Dynamics Simulations

Abstract: Metal–organic frameworks (MOFs) are a family of materials that have high porosity and structural tunability and hold great potential in various applications, many of which require a proper understanding of the thermal transport properties. Molecular dynamics (MD) simulations play an important role in characterizing the thermal transport properties of various materials. However, due to the complexity of the structures, it is difficult to construct accurate empirical interatomic potentials for reliable MD simula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 70 publications
2
14
0
Order By: Relevance
“…We used the homogeneous non-equilibrium molecular dynamics (HNEMD) method [33] to calculated the thermal conductivity. The MD simulation details are consistent with the previous work [27] and the relevant inputs are given in appendix C. A driving force with a parameter F e = 2 × 10 −4 Å −1 was used to drive the system out of equilibrium, and we have confirmed that it is sufficiently small to keep the system within the linear-response regime. To be consistent with the previous work [27], we have used a supercell with 5 × 5 × 5 conventional cells (53 000 atoms), which was tested to be sufficiently large to eliminate finite-size effects.…”
Section: Applications To Heat Transport In Mofssupporting
confidence: 54%
See 2 more Smart Citations
“…We used the homogeneous non-equilibrium molecular dynamics (HNEMD) method [33] to calculated the thermal conductivity. The MD simulation details are consistent with the previous work [27] and the relevant inputs are given in appendix C. A driving force with a parameter F e = 2 × 10 −4 Å −1 was used to drive the system out of equilibrium, and we have confirmed that it is sufficiently small to keep the system within the linear-response regime. To be consistent with the previous work [27], we have used a supercell with 5 × 5 × 5 conventional cells (53 000 atoms), which was tested to be sufficiently large to eliminate finite-size effects.…”
Section: Applications To Heat Transport In Mofssupporting
confidence: 54%
“…To confirm the correctness of our GPU implementation of D3 in gpumd and to evaluate the effects of cutoffs, we take three MOF materials (MOF-5, ZIF-8, and HKUST-1) as studied before using NEP models [27] and compare the calculated forces to those from vasp (using the IVDW = 12 option). The results are shown in figure 1.…”
Section: Implementation Of the D3 Dispersion Correction Into Gpumdmentioning
confidence: 99%
See 1 more Smart Citation
“…28 To date, only a few MLPs for MOFs have been reported, exclusively for 3D MOFs, including UiO-66, MOF-5, ZIF-8, and MOF-74. 31–35 Herein, systematic phonon spectrum calculations and first-principles MD simulations first revealed that the proposed 2D MOF material does not exhibit any imaginary phonon modes in the whole Brillouin zone and that it can maintain its structural integrity at room temperature as well as in an aqueous solution. Large-scale modelling of the MOF system, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…To overcome its shortcomings, four other works relied on periodic DFT calculations on the primitive cell of the framework to train their NNP. 25,29–31 An option proposed by Vandenhaute et al 29 to solve the high computational cost of running ab initio simulations with large unit cells, was to use a data-efficient NNP (NequIP 32 ) to reduce the number of ab initio calculations. Interestingly, this work also demonstrated that it was possible to simulate a phase transition for MOFs with MLPs, although the transition was non-displacive and did not involve any bond breaking.…”
Section: Introductionmentioning
confidence: 99%